Mirror‐Image 5S Ribonucleoprotein Complexes. Issue 9 (21st January 2020) - Ling, Jun‐Jie; Fan, Chuyao; Qin, Hong; Wang, Min; Chen, Ji; Wittung‐Stafshede, Pernilla; Zhu, Ting F.
Abstract: After realizing mirror‐image genetic replication, transcription, and reverse transcription, the biggest challenge in establishing a mirror‐image version of the central dogma is to build a mirror‐image ribosome‐based translation machine. Here, we chemically synthesized the natural and mirror‐image versions of three ribosomal proteins (L5, L18, and L25) in the large subunit of the Escherichia coli ribosome with post‐translational modifications. We show that the synthetic mirror‐image proteins can fold in vitro despite limited efficiency and assemble with enzymatically transcribed mirror‐image 5S ribosomal RNA into ribonucleoprotein complexes. In addition, the RNA–protein interactions are chiral‐specific in that the mirror‐image ribosomal proteins do not bind with natural 5S ribosomal RNA and vice versa. The synthesis and assembly of mirror‐image 5S ribonucleoprotein complexes are important steps towards building a functional mirror‐image ribosome. Abstract : The natural and mirror‐image versions of three ribosomal proteins (L5, L18, and L25) were chemically synthesized with post‐translational modifications. The synthetic mirror‐image proteins can fold in vitro despite limited efficiency and assemble with enzymatically transcribed mirror‐image 5S ribosomal RNA into ribonucleoprotein complexes.